PENGARUH EKUITAS MEREK, NILAI DAN RELASIONAL TERHADAP LOYALITAS KONSUMEN SWALAYAN DI KOTA BANDA ACEH - Agus Rianto, Mukhlis Yunus (Departemen Manajemen, 2019)
Abstract: This study aims to measure the effect of brand, value and relational equity on self-service consumer loyalty in the city of Banda Aceh. The sample used in this study were consumers who had shopped, still shopping and would continue to shop at the Banda Aceh City Supermarket, which numbered 150 respondents. Data collection equipment used in this research is questionnaire. The sampling technique used is non-probability sampling. Partial least square (PLS) is used as an analytical method to determine the effect of all the variables involved. Based on the results of the PLS analysis, indicates that: 1) Brand, Value and Relational Equity influence Consumer Loyalty, 2) Brand Equity influences Consumer Loyalty, 3) Value Equity influences Consumer Loyalty, 4) Relational Equity affects consumer loyalty .